Forestry and wood technology research and education network for climate change adaptation strategies and ASFORCLIC - HORIZON 2020 project - Kyriaki Giagli; Kathrin Böhling; Tobias Mette; Aleš Kučera; Torben Hilmers; Petr Čermák (Les)
Seven European universities and research institutions from four countries agreed to collaborate on the ASFORCLIC - HORIZON 2020 project to support the ambitious goals of raising the leading institution's MENDELU research profile and strengthening its research excellence in the highly demanding field of assessing the impact of global climate change on forests and the bio-based sector. The ASFORCLIC consortium evaluates possible risk factors, predicts their evolution, and develops adaption strategies for future applications to monitor the impact of global climate change on central European forestry, particularly Czech forestry. Facing the unprecedented challenge of implementing a mobility project during the COVID-19 pandemic, the consortium used strategic approaches and augmented offerings, including successful literature seminars, writing workshops, and advanced data evaluation training largely realized through virtual platforms.